Conceptual analysis of social innovation in the field of applied social sciences: A bibliometric review of the literature - Antônio de Lima, Anderson; Ribeiro , Thiago de Luca Santana; Lavio de Oliveira, Marcos Antonio Maia (Journal of Sustainable Competitive Intelligence, 2024)
Purpose: This study aims to map the formation and theoretical conceptual evolution of social innovation in the field of applied social sciences, as well as to provide an integrated framework on the most influential studies in this field and trends in future studies on the subject. Methodology/approach: A bibliometric analysis is carried out to identify the most influential studies, the themes (clusters) of studies in the area and trends in future studies. Originality/Relevance: The bibliometric review carried out in this research allowed us to identify, through the co-citation map, the intellectual structure that guides the evolution of studies on corporate social innovation in the field of applied social sciences. Key findings: The bibliographic pairing identified five clusters: Value Co-creation, Co-production and Attributes that Enhance Social Innovation; Conceptual Models and Frameworks of Social Innovation; Sharing Economy and New Challenges and Opportunities in Social Innovation Research; The Effects of Social Entrepreneurship on Social Innovation; and The Importance of Institutional Aspects in Supporting Social Innovation. Theoretical/methodological contributions: Our findings provide an integrated view. Co-creation and co-production emphasize the value of collaboration between social actors, while the conceptual models provide a theoretical framework to understand and guide innovative practices. The sharing economy emerges as a transformative scenario, offering new opportunities and challenges in a digital world, and social entrepreneurship directly contributes to innovation by applying creative solutions to social problems.